Longitudinal Study of the (Un-)Political Representation of Israel in German Textbooks - Uhlenwinkel, Anke (Journal of Geography Education, 2023)
This article shows that and how the representation of Israel in German textbooks has changed since the 1970s. Drivers of change are not only changing social conditions and perceptions, but also pedagogical approaches that contribute to a different evaluation of the content in the context of an implicated coherence. In addition, the establishment of German unity in 1990 brought almost contradictory assessments of the conflict between Israelis and Palestinians into discussion with each other.
Keywords: textbook, representation of Israel, geographical concepts, tasks, reading competence